Two paradigms for divine healing : Fred F. Bosworth, Kenneth E. Hagin, Agnes Sanford, and Francis MacNutt in dialogue - Hejzlar, Pavel. (Global Pentecostal and Charismatic Studies, 2010)
The doctrine and practice of healing through faith has been a hallmark of Pentecostalism since its inception and helps to account for the widespread appeal of the movement. While "divine healing," as it is called by insiders, has brought hope to the sick, it has also been a source of disenchantment and controversy. The present study offers a close look at the teaching of four major ministers of healing in the twentieth-century United States. The author distinguishes between the healing evangelists and pastoral ministers of healing who react to them. This book discusses in detail the merits of both schools and the author proposes a solution to the problems inherent in the two paradigms under scrutiny.